A description of the characteristics of shallot farmers using pesticides. (April 2020) - Winarni, S; Susanto, H; Kartini, A; Suwondo, A; Nissa, C; Dharminto,
Abstract: The biggest use of pesticides is in the Brebes Regency, which is an onion farmer. Farmers in Brebes use a mixture of more than 5 types of pesticides. At the onion pest season, farmers can spray pesticides every 2 days. The results of research on pesticide residues in the soil show that the soil in Brebes still contains chlorpyrifos residues from 0.39 to 0.72 mg/kg. On average, farmers spray onions 15-20 times during the planting period, which is about 2 months. The most widely usage of pesticide is in Dursban 200 EC. This study aims to look at the characteristics of sprayers male farmers and the use of pesticides. The population of shallot male farmers are sprayers male farmers who live in the villages of Pamulihan, Larangan, Siandong, Rengaspendawa, and Sitanggal. The control sample is taken randomly while the case sample is taken by purposive sampling. The results obtain that the majority of respondents''s education is elementary school graduation (40%), have no history of chronic illness (76%), BMI (Body Mass Index) normal (64%), smoking (66.7%), not drinking alcohol (65.3%), the average spraying frequency is ≥ 3 times a week. The use of high dosage of pesticides (> 183.12 cc) was most in the control group at 66.0% compared to case group 44.0%. The agricultural activities that cover all activities from planting to harvest are mostly carried out by the case group at 100% compared to 97.3% of control group. Much personal protective equipment (PPE) is not used when spraying. The storage distance of shallots is ≤ 5 meters from the gathering place of the family. At the time of spraying, the opposite direction when spraying is more in case respondents at 28.0% compared to 26.0% controls. Post-harvest spraying is performed more in cases with 52.0% compared to 40% in controls. The use of spraying clothes that are the same as clothes worn at home was more in the control group which was 72.0%. The behaviour of not handwashing with soap after spraying pesticides is mostly carried out by case group at 92.0%. Information and education related to pesticide usage is still needed.